Functional outcomes and complications of open elbow dislocations - Schnetzke, Marc; Porschke, Felix; Kneser, Ulrich; Studier-Fischer, Stefan; Grützner, Paul Alfred; Gühring, Thorsten (Obere Extremität, 2018)
Background - The current study investigated the clinical outcome of open elbow dislocations, focusing on the influence of associated soft tissue and bone injury. - Patients and methods - From October 2008 to August 2015, 230 patients with elbow dislocations were treated at the study center. Our retrospective study comprised 21 cases of open elbow dislocations. The mean age of patients was 49 years (20-83 years); there were six (29%) female and 15 (71%) male patients. The range of motion (ROM) of the injured and uninjured elbow was measured, and the Mayo Elbow Performance Score (MEPS), Mayo Wrist Score (MWS), and Disability of Arm, Shoulder and Hand (DASH) score were assessed. Complications and revision surgeries were recorded. The influence of the severity of soft tissue injury (I°/II° open vs. III° open) and type of dislocation (simple vs. complex) was evaluated. - Results - After a 57-month follow-up (range, 24-98 months), the mean DASH score was 20± 15, the MEPS was 82± 11, and the MWS was 74± 22. The ROM of the injured elbow was significantly decreased compared with the uninjured one (arc of ulnohumeral motion: 104° vs. 137°; p= 0.001). Patients with I°/II° open elbow dislocations had a better clinical outcome according to the MEPS (86± 11 vs. 76± 9; p= 0.045) and a comparable outcome according to the DASH score (19± 18 vs. 21± 9; p= 0.238). In all, 11 patients (52%) had postoperative complications and 11 patients underwent at least one revision surgery. Complex elbow dislocations had significantly more complications and revision surgeries than simple dislocations (77% vs. 13%; p= 0.008). - Conclusion - Favorable clinical outcomes can be achieved after treatment of open elbow dislocations. These injuries are prone to neurovascular damage and complex dislocations are linked to high rates of complications and revision surgeries.
Published online 2018 Jun 11
Gesehen am 08.04.2020